2021
DOI: 10.1016/j.scitotenv.2021.147486
|View full text |Cite
|
Sign up to set email alerts
|

COVID lessons from the global south – Face masks invading tourist beaches and recommendations for the outdoor seasons

Abstract: In response to the COVID-19 pandemic in 2020, Personal Protective Equipment (PPE) has been extensively used, and discarded PPE has been observed in many different environments, including on tourist beaches. Here we examined the distribution and densities of face masks on some of the main tourist beaches in Chile, and we monitored their daily accumulation rates on one beach in northern-central Chile. Face masks were found on beaches across the country with average densities of 0.006 ± 0.002 (mean ± se) face mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 37 publications
5
48
1
2
Order By: Relevance
“… Ardusso et al (2021) indicated that the use and mismanagement of personal protective equipment (PPE) represented an environment problem and the increase in the use of single-use plastic aggravated plastic pollution on beaches. Thiel et al (2021) examined the distribution and densities of masks on some tourist beaches in Chile, and promoted to provide enough PPE-related signs and waste bins and set up strict waste rules. Alfonso et al (2021) assessed regulations and strategies to abate the problem of plastic pollution in beaches during the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Ardusso et al (2021) indicated that the use and mismanagement of personal protective equipment (PPE) represented an environment problem and the increase in the use of single-use plastic aggravated plastic pollution on beaches. Thiel et al (2021) examined the distribution and densities of masks on some tourist beaches in Chile, and promoted to provide enough PPE-related signs and waste bins and set up strict waste rules. Alfonso et al (2021) assessed regulations and strategies to abate the problem of plastic pollution in beaches during the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, large volumes of PPE waste have been generated and inadequately discharged during this pandemic ( Mekonnen and Aragaw, 2021 , De-la-Torre and Aragaw, 2021 ). This type of waste has become a severe environmental concern since it has been evidenced in rivers, beaches, coasts, lakes, and cities worldwide ( Ardusso et al, 2021 , Akhbarizadeh et al, 2021a , Ben Haddad et al, 2021 , Okuku et al, 2020 , Rakib et al, 2021 , Thiel et al, 2021 ), potentially representing a new major type of plastic pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, one study reported the abundance of face masks along the coast of Chile, while discussing the influence of COVID-19 infrastructure (signposts for PPE, PPE-specific bins, etc.) ( Thiel et al, 2021 ). Other studies have quantified PPE pollution in very specific sites/cities rather than executing a broader survey ( Gallo Neto et al, 2021 , De-la-Torre et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…( Botetzagias and Malesios, 2021 ) Location Sampling sites Number of items Reference Lima; Peru 11 beaches 7.44 × 10 −4 items/m 2 ( De-la-Torre et al, 2021 ) Jacarta bay; Indonesia Cilincing and Marunda river mouths ∼254.7 - 246 items/day ( Cordova et al, 2021 ) Kwale, Kilifi, Mombasa; Kenya Beaches (sediments and water), and streets Streets: 0.01 item/m 2 Beaches: 0.1 items/m 2 ( Okuku et al, 2021 ) Soko island; Japan 100 m beach 7 × 10 −3 items/m 2 ( Stokes, 2020 ) Cox's Bazar; Bangladesh One beach (13 sampling sites; 12 weeks) 6.29 × 10 −4 items /m 2 ( Rakib et al, 2021 ) Bushehr; Iran Sandy beaches (S1, S4, S7-S9) Rocky beaches (S3, S5, S6) ∼54 items/m 2 for 40 days ( Akhbarizadeh et al, 2021 ) Toronto; Canada Parking lots, hospitals, residential areas 0.001 items/m 2 /day or 6.5 items/day. Parking lots and hospitals (1.60-1.33 × 10 −3 items/m 2 ) Residential areas (2.9-2.7 × 10 −4 /m 2 ) ( Ammendolia et al, 2021 ) Chile 12 tourist beaches from northern and central Chile 0.006 ± 0.002 items/m 2 ( Thiel et al, 2021 ) Cape Town and Durban; South Africa Urban environments 2271 (11.4±4.4 items/100 m/∙day) to 3741 items (18.7 ± 9.6 items/100 m/∙day) but <1% comprised PPE. ( Ryan et al, 2020 ) …”
Section: Final Remarks and Future Perspectivesmentioning
confidence: 99%